2017
DOI: 10.1093/ajh/hpx116
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Levels Are Associated With Circadian Blood Pressure Variation in Chinese Hypertensive Adults

Abstract: These results indicated that high homocysteine levels associate with disturbed circadian BP variation in Chinese hypertensive adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Differences between these studies might be explained by the participants’ ethnicities. Total plasma Hcy levels have significant gender‐dependent differences although the conclusions of the previous studies were conflicting …”
Section: Discussionsupporting
confidence: 90%
“…Differences between these studies might be explained by the participants’ ethnicities. Total plasma Hcy levels have significant gender‐dependent differences although the conclusions of the previous studies were conflicting …”
Section: Discussionsupporting
confidence: 90%
“…Investigators have reported a significant association of serum Hcy with different indices of arterial stiffness such as pulse pressure and aortic stiffness in the general population 4 and in elderly patients who have multiple cardiovascular risk factors 7 . Moreover, Hcy was associated with non‐dipping BP pattern, a potent predictor of cardiovascular mortality and morbidity in hypertensive individuals 8 . Plasma Hcy concentrations correlated with the incidence of cardiovascular, cerebrovascular, and peripheral artery disease 9 and atherosclerotic vascular damage 10 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, Hcy was associated with non‐dipping BP pattern, a potent predictor of cardiovascular mortality and morbidity in hypertensive individuals. 8 Plasma Hcy concentrations correlated with the incidence of cardiovascular, cerebrovascular, and peripheral artery disease 9 and atherosclerotic vascular damage. 10 In addition, hyper‐homocysteinemia (hHcy) was associated with peripheral microvascular endothelial dysfunction and a Hcy level of >10 µmol/L was significantly associated with all‐cause mortality and atherosclerotic cardiovascular events in older obese and hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies have been confirmed in the work of Dong Yi-Fey et al [61]. These authors randomly selected 244 patients with normal nighttime blood pressure drop (blood pressure drop greater than 10%, dippers) and 249 patients with abnormal nighttime blood pressure drop (nondippers) from 5,223 hypertensive patients.…”
Section: Homocysteine and Night-time Blood Pressure Dropmentioning
confidence: 61%